Desain Pengembangan Buku Ajar Bahasa Arab Berbasis Permainan Edukatif Gramatikal Bahasa Arab - Maulidi, Maulidi; Aisa, Aufia (LPPM Universitas KH.A. Wahab Hasbullah, 2023)
The need for textbook materials is very important in following up on the continuity of scientific transformation. This study aims to determine the development of Arabic language textbook materials for MA Al-Bairuny students by using needs analysis and validating the feasibility of textbook materials with a communicative approach according to experts. The researcher developed this educational game-based textbook which aims to make it easier for students to understand, especially in Arabic grammar, not only theoretical but also practical and communicative. Data collection techniques using observation, questionnaires, interviews, and documentation. The method used in this research is R&D adopting the ADDIE development model (analysis, design, develop, implementation, evaluation). The Educational Game book is a product of textbook materials produced through needs analysis and input from experts. The test results of this book indicate that this book is effective in meeting the needs of students in improving Arabic language competence through mastery of Arabic grammar in their learning materials.